Optimized liquid chromatography-electrospray quadrupole linear ion trap mass spectrometry method for the quantitation of paraquat in plasma: application to a toxicokinetic study. Issue 21 (15th May 2019) - Fan, Jiaming; Li, Pengfei; Liu, He; Zhao, Rui; Zhao, Zhixia; Du, Ping; Liu, Lihong
Abstract : A convenient and sensitive LC-MS/MS method fitting for toxicokinetics study was validated for quantitation of paraquat in rat plasma. Abstract : Paraquat is a kind of quaternary ammonium herbicide used to the broadest extent in the world; the poisoning of paraquat has a high mortality rate. In this paper, a convenient and sensitive method was developed for the quantitation of paraquat in biological samples by LC-MS/MS with a simple run time of 4 min. Prior to extraction, an isotopically labeled internal standard, i.e., paraquat- d 8 was added. Then, a one-step protein precipitation was employed. A Thermo Acclaim Trinity Q1 column achieved a better separation efficiency of paraquat and the biological matrix. Moreover, the concentration of the ammonium salt in the mobile phase using the Q1 column was lower, which could effectively reduce the damage of a high concentration of ammonium salt to the mass spectrometer. The calibration curve was linear over the concentration range of 1.00–100.00 ng mL −1 . The limit of quantification was 1.00 ng mL −1 and better than most of the previously reported values. The intra- and inter-day accuracies were within the range of 97.46–112.94%, and the intra- and inter-day precisions were less than 6.90% and 7.20%, respectively, for plasma. The matrix effects of plasma were negligible. After oral administration at a single dose of 90 mg kg −1, paraquat was found to be quickly absorbed and the average T max value was 0.79 h. The average C max value was 11.58 μg mL −1 and AUC0–last was 42.13 μg h mL −1 . The average t 1/2 and MRT0–last values were 12.69 h and 13.05 h, respectively. The method was successfully applied to determine the concentration of paraquat in rat plasma and was well suited for the toxicokinetic study.